An operational model for implementing conservation action - Knight, A.; Cowling, R.M.; Campbell, Bruce M. (2006)
The preoccupation of many conservation planners with the refinement of systematic assessment techniques has manifested an “implementation crisis” in conservation planning. This preoccupation has provided systematic assessments with well-tested tools (e.g., area selection algorithms) and principles (e.g., representation, complementarity), but our understanding of these techniques currently far exceeds our ability to apply them effectively to pragmatic conservation problems. The science is informative about where one needs to do conservation, but silent on how to achieve it. Operational models, defined as simplified conceptualizations of processes for implementing conservation action at priority conservation areas, are essential for guiding conservation planning initiatives because they assist understanding of how these processes function. Operational models developed to date have largely been linear, simplistic, and focused on the systematic assessment of biological entities. Experience in the real world indicates that operational models for conducting conservation planning initiatives should explicitly complement a systematic conservation assessment with activities that empower individuals and institutions (enabling) and explicitly aim to secure conservation action (implementation). Specifically, implementing effective conservation action requires that systematic assessments be integrated functionally with a process for developing an implementation strategy and processes for stakeholder collaboration while maintaining a broad focus on the implementation of conservation action. A suite of hallmarks define effective operational models (e.g., stakeholder collaboration, links with land-use planning, social learning, and action research). Greater development and testing of the practical application of operational models should lead to higher levels of effective implementation and alleviate the implementation crisis. Social learning institutions are essential for ensuring ongoing improvement in the development and application of operational models that deliver effective conservation action.